A systematic review of functional analysis in pediatric feeding disorders. Issue 4 (15th September 2019) - Saini, Valdeep; Kadey, Heather J.; Paszek, Katherine J.; Roane, Henry S.
Abstract : We conducted a systematic review of the functional analysis of inappropriate mealtime behavior in peer‐reviewed studies in PsycINFO, ERIC, PubMed, and the Journal of Applied Behavior Analysis between 2000‐2016. We identified 18 studies involving 86 functional analyses. We coded descriptive data and calculated summary statistics in addition to conducting a quality appraisal of the literature. We identified escape, exclusively or in part, as the maintaining reinforcer for inappropriate mealtime behavior in 92% of cases. Results indicate that differentiated functional analyses of inappropriate mealtime behavior can be obtained, and outcomes are consistent with etiological theories of food refusal behavior. We discuss procedural differences across studies as well as directions for future research.